Assessing Reliability in Manufacturing Systems by a New Arrangement of the Mean Time Between Failures (MTBF) - Kadir, Abdulkhalek M. (Al-Nahrain Journal for Engineering Sciences, 2025)
This work has studied the size of the mean time between failures (MTBF) because it has a vital role in assessing reliability in manufacturing systems. Previous studies have indicated that the reliability value depends on the size of MTBF, so they indicated only 11 types of time that reliability value depends on, and they used methods of DFR and RCM to enhance the reliability level. To assess and increase reliability value, this work referred to the four main times: mean time between failures (MTBF), mean time to diagnosis (MTTD), mean time to repair (MTTR), and mean time to failure (MTTF) in more detail. Also, it designed a new arrangement of failure notification time, failure diagnosis time, downtime, failure repair, testing time, and recovery periods for ongoing operations in manufacturing systems through a new redistribution of 19 times and time intervals in detail between the four main times, so it revealed and added 8 types of other times and time intervals more than previous studies because they have vital roles in increasing reliability value. Thus, the new arrangement contains two parallel pathways and 19 types of times and time intervals. The first pathway represents 5 positions and 11 types of start and end times; the second pathway represents 4 positions and 8 time intervals. Consequently, MTBF becomes longer because the new arrangement shortens the time distances between the start of failure and repair process end, between diagnosis end and test, and between inspection end and the system’s return to normal operating conditions. The motivations are to raise the reliability value, quality level, and effective maintenance and save costs. This work used the data collection and analysis method. The results showed that there is a higher reliability for manufacturing systems when the time arrangement is better, MTBF is longer, MTTD is shorter, MTTR is smaller, MTTF is longer, and the error rate is lower.